Persepsi Pengunjung Terhadap Fasilitas, Kondisi Lingkungan, Dan Kesediaan Membayar Pada Objek Wisata Taman Hewan Pematang Siantar - Armitha Silalahi; Mifthahul Jannah; Rika Ardhana; Aulia Rahma; Fernaendi Girsang; Samyel Saragih; Pawer Panjaitan (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine visitor perceptions of facilities, ecological quality, and willingness to pay at the PematangSiantar Animal Park. (THPS). This research was conducted in June 2023. This research was carried out using a qualitative approach. Data was collected through interviews with respondents, namely THPS visitors. The selection of respondents was carried out randomly and analyzed using a qualitative descriptive technique. The visitor's perception of the THPS facility is quite good although there are some things that need to be improved. The main reason visitors come to THPS is to see various types of animals (100%). 100% of respondents agreed that THPS management wore an entrance ticket and almost all visitors (92%) were willing to pay IDR 30,000. However, THPS management needs to set affordable ticket prices for visitors. The results of the qualitative analysis show that from the aspect of visitor satisfaction, they still need lots of promo tickets for visitors.